STRATEGI PENGELOLAAN KELAS DALAM PEMBELAJARAN PENDIDIKAN AGAMA ISLAM PADA ERA NEW NORMAL DI SMA NEGERI 1 MALANG - Anisa Fitria Ramadanti; Mohammad Afifulloh; Dian Mohammad Hakim (VICRATINA, 2022)
Education is a very important basis for preparing the nation's golden generation on theera of globalization. The learning carried out is a provision to get the best lessons toachieve a meaningful education and learning. As the Covid-19 cases subsided, thegovernment issued a new normal policy. Through this policy, educational units may carryout face-to-face learning provided that health protocols are always applied. Where in oneclassroom only contains 50% class capacity, so that in one class is divided into two studygroups. Therefore, the teacher must have a special strategy in managing the class so thatthey still has a conducive and optimal atmosphere. The type of this research is adescriptive-qualitative approach. The data collection method used are conductingobservations, interviews, and documentation. The data sources in this study wereteachers of Islamic religious education subjects. The analysis technique used by this isexamining all available data from various sources. This study aims to determine theclassroom management strategy in learning Islamic religious education in the newnormal era at SMA Negeri 1 Malang, to define the management of the physical and socialenvironment of students, and obstacles in classroom management at SMA Negeri 1Malang.